Pampanga's Tibok-tibok its traditional process operation, inherent problems and improvements - Santos, Janina C. (College of Home Economics, University of the Philippines Diliman, 2013)
Tibok-tibok or sweet carabao milk pudding, is a native delicacy unique to the Province of Pampanga. It is basically produced from pure carabao's milk, coconut milk to make the topping latik and rice flour, with very short shelf life of less than a day at room temperature. The traditional process have been passed on from may generations, with modifications in between such that current practice of producing tibok-tibok is far less better than its original, as quick substitutes like cornstarch, pasteurized fresh milk or even evaporated milk have been used to perhaps decrease the cost and time of preparation. A documentation of the current state of tibok-tibok processing and an analysis of the physicochemical, microbiological, and sensory attributes was conducted to serve as base line data for current and future improvements of the product. Out of all the establishments in Pampanga, very few make tibok-tibok using carabao's milk and rice flour. A comparison of the two formulations (glutinous rice flour versus cornstarch) based on physico-chemical, microbiological, and consumer sensory test showed that pH, % titrable acidity, water activity and microbial count were not significantly different (p>0.05) but in terms of consumer acceptance, tibok-tibok thickened with cornstarch was more acceptable (p<0.05) to the panelists. Syneresis was evident for both samples upon storage at refrigerated temperatures.